PENGGUNAAN EDUCANDY SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN IPS TERHADAP KEMAMPUAN KOLABORATIF DAN CAPAIAN PEMBELAJARAN PADA SISWA KELAS VII DI SMP LABSCHOOL UNESA 2 - Irfana Nuril Fadhilah; Agus Suprijono; Sukma Perdana Prasetya; Silvi Nur Afifah (STKIP Subang, 2026)
Efforts to improve students' collaborative skills and learning achievement in Social Studies (IPS) require the integration of technology-based interactive learning media capable of creating a more active, participatory, and meaningful learning process. This study aimed to analyze the effect of using Educandy as an interactive learning medium on the collaborative skills and learning achievement of seventh-grade students at SMP Labschool UNESA 2. A quantitative approach employing a pretest-posttest control group design was adopted in this study. The research sample consisted of Class VII A as the experimental group, which received instruction using Educandy, and Class VII B as the control group, which was taught using PowerPoint as the instructional medium. Data were collected through achievement tests, questionnaires, and documentation. The data were analyzed using validity and reliability tests, normality, homogeneity, and linearity tests, simple linear regression analysis, an independent samples t-test, and the N-Gain test. The findings revealed that the use of Educandy had a positive and statistically significant effect on students' collaborative skills, with a significance value of 0.001 (p < 0.05) and a coefficient of determination (R²) of 32.6%. Furthermore, Educandy also demonstrated a positive and significant effect on students' learning achievement, with a significance value of 0.001 (p < 0.05) and an R² value of 52.9%. The N-Gain analysis indicated that the experimental group achieved a high level of improvement in learning achievement (71.15%), whereas the control group demonstrated a moderate level of improvement (55.77%). Students' responses toward the implementation of Educandy obtained an average score of 77.25%, which was categorized as good. These findings suggest that Educandy is an effective interactive learning medium for enhancing students' collaborative skills and learning achievement in Social Studies and has the potential to serve as an innovative instructional alternative that supports the implementation of twenty-first-century learning.